Mineral Commodity Summaries 1992 - Significant Events In 1991 (The National Institute for Occupational Safety and Health (NIOSH), 1992)
The value of processed materials of mineral origin was estimated to have exceeded $297 billion in 1991. U.S. raw non fuel minerals production in 1991 was estimated at $30.8 billion, a 5.8% decline from that in 1990. This estimate was based on data for the first quarter of 1991 (in some cases two quarters) for most of the 21 minerals that for many years have accounted for more than 95% of the industry's production value. The value of minerals production has increased in all but 4 of the last 30 years. The metals component of production value has fluctuated much more than the industrial minerals component, reflecting the greater volatility of metal prices. Employment in metal mining rose slightly in 1991, but this gain was more than offset by a decline in employment in industrial mineral mining, resulting in an overall decline of 3.0% to 164,600 workers in 1991. Prices of several major metals declined during 1991, reflecting weakness in the economy, causing some metal mines to shut down or reduce operations.